Pharmacogenetics of Bleeding and Thromboembolic Events in Direct Oral Anticoagulant Users. Issue 3 (26th June 2021) - Lähteenmäki, Jaakko; Vuorinen, Anna‐Leena; Pajula, Juha; Harno, Kari; Lehto, Mika; Niemi, Mikko; van Gils, Mark
Abstract : This study aimed to analyze associations between genetic variants and the occurrence of clinical outcomes in dabigatran, apixaban, and rivaroxaban users. This was a retrospective real‐world study linking genotype data of three Finnish biobanks with national register data on drug dispensations and healthcare encounters. We investigated several single‐nucleotide variants (SNVs) in the ABCG2, ABCB1, CES1, and CYP3A5 genes potentially associated with bleeding or thromboembolic events in direct oral anticoagulant (DOAC) users based on earlier research. We used Cox regression models to compare the incidence of clinical outcomes between carriers and noncarriers of the SNVs or haplotypes. In total, 1, 806 patients on apixaban, dabigatran, or rivaroxaban were studied. The ABCB1 c.3435C>T (p.Ile1145=, rs1045642) SNV (hazard ratio (HR) 0.42, 95% confidence interval (CI), 0.18–0.98, P = 0.044) and 1236T‐2677T‐3435T (rs1128503‐rs2032582‐rs1045642) haplotype (HR 0.44, 95% CI, 0.20–0.95, P = 0.036) were associated with a reduced risk for thromboembolic outcomes, and the 1236C‐2677G‐3435C (HR 2.55, 95% CI, 1.03–6.36, P = 0.044) and 1236T‐2677G‐3435C (HR 5.88, 95% CI, 2.35–14.72, P < 0.001) haplotypes with an increased risk for thromboembolic outcomes in rivaroxaban users. The ABCB1 c.2482‐2236G>A (rs4148738) SNV associated with a lower risk for bleeding events (HR 0.37, 95% CI, 0.16–0.89, P = 0.025) in apixaban users. ABCB1 variants are potential factors affecting thromboembolic events in rivaroxaban users and bleeding events in apixaban users. Studies with larger numbers of patients are warranted for comprehensive assessment of the pharmacogenetic associations of DOACs and their relevance for clinical practice.